2020
DOI: 10.1016/j.jmgm.2020.107680
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of short synthetic antifreeze peptides: Insights into ice-pinning mechanism

Abstract: Organisms living in icy environments produce antifreeze proteins to control ice growth and recrystallization. It has been proposed that these molecules pin the surface of ice crystals, thus inducing the formation of a curved surface that arrests crystal growth. Such proteins are very appealing for many potential applications in food industry, material science and cryoconservation of organs and tissues. Unfortunately, their structural complexity has seriously hampered their practical use, while efficient and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…After adsorption, it was determined that, any surface of AFPs can bind to ice by hydrogen bonds. Similar results were shown experimentally and by simulation in the study by Gandini et al. (2020) .…”
Section: Fundamentals Of Antifreeze Proteinssupporting
confidence: 90%
“…After adsorption, it was determined that, any surface of AFPs can bind to ice by hydrogen bonds. Similar results were shown experimentally and by simulation in the study by Gandini et al. (2020) .…”
Section: Fundamentals Of Antifreeze Proteinssupporting
confidence: 90%
“…As the simulation process continued, it can be clearly observed that the MNPs tend to become concentrated close to the ice crystal surface gradually after the magnetic field was added, and the combination of MNPs and ice crystals could destroy the ice crystal surface. The crystal growth was found to be significantly affected by the crystal interface structure 37 . The addition of MNPs was observed to destroy the interfacial structure of the ice crystal crystals and the symmetry of the crystal planes, which caused significant steric hindrance to the docking of free water molecules and made the ice crystal growth more difficult.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal growth was found to be significantly affected by the crystal interface structure. 37 The addition of MNPs was observed to destroy the interfacial structure of the ice crystal crystals and the symmetry of the crystal planes, which caused significant steric hindrance to the docking of free water molecules and made the ice crystal growth more difficult. A number of previous studies have shown that the growth rate of ice crystals containing nanoparticles was lower than that of the pure water, thereby indicating that the nanoparticles near the interface can effectively hinder the growth of ice crystals.…”
Section: Analyses Of Protein Conformation Dynamic Rheologicalmentioning
confidence: 99%